Radical Chemistry in a Femtosecond Laser Plasma: Photochemical Reduction of Ag(+) in Liquid Ammonia Solution - Meader, Victoria Kathryn (Molecules, 2018)
Plasmas with dense concentrations of reactive species such as hydrated electrons and hydroxyl radicals are generated from focusing intense femtosecond laser pulses into aqueous media. These radical species can reduce metal ions such as Au(3+) to form metal nanoparticles (NPs). However, the formation of H(2)O(2) by the recombination of hydroxyl radicals inhibits the reduction of Ag(+) through back-oxidation. This work has explored the control of hydroxyl radical chemistry in a femtosecond laser-generated plasma through the addition of liquid ammonia. The irradiation of liquid ammonia solutions resulted in a reaction between NH(3) and OH·, forming peroxynitrite and ONOO(−), and significantly reducing the amount of H(2)O(2) generated. Varying the liquid ammonia concentration controlled the Ag(+) reduction rate, forming 12.7 ± 4.9 nm silver nanoparticles at the optimal ammonia concentration. The photochemical mechanisms underlying peroxynitrite formation and Ag(+) reduction are discussed.